Identifying factor of e-business adoption among homestay operators in Kuching, Sarawak: Qualitative study / Rebecca Dian...[et al.] - Dian, Rebecca; Kasuma, Jati; Adenan, Mohd Amirul; Nordin, Jennifah; Awang Masjar, Dayang nur Atikah (Universiti Teknologi MARA, Kedah, 2018)
The purpose of this study is to identify the factors of e-business adoption by homestay operators in Kuching, Sarawak. Homestay is known as a private home that tourists rent where the owners would provide the facilities and comforts that gives the tourist a similar feeling of staying in their own house and they would have the chance to interact with nearby community as well. Entrepreneurs in Malaysia nowadays are steadily taking part in this particular business as it can be seen as a second job for them to get extra income. Entrepreneur practices e-business in their business management. E-business is the administration of conducting business via internet. This would include the buying and selling of goods and services, along with providing technical or customer support through the internet. However, not all entrepreneurs know how to take advantages from conducting e-businessas e-business are still not fully utilized among homestay operators. This research involves 10 homestay operators as key respondents by using semi-structured interview. The findings revealed that there are four factors identified that influence entrepreneurs to use e-business: the gaps of age homestay operators on their communication style, the knowledge and experience of homestay operators, e-business awareness among homestay operators, and business location in term of their internet accessibility